Safety and hazards during the welding process-A review - Arman Malik (Journal of Welding Technology, 2026)
The basic objective of this review paper is to understand and highlight the safety aspects and various hazards during the welding process, and to raise awareness of these hazards so we can avoid them. The welding process is extensively used in various industries such as the petrochemical, chemical industries, automobile, and manufacturing industries. It is widely used process all over the world but as it is widely used and important process, it causes hazards too for the workers. However, the very energy density required to fuse metals introduces significant occupational safety and health (OSH) hazards. This review paper systematically examines the multifaceted risks inherent in the welding environment.  Hazard generated during the welding process is risky to human life, knowledge of occupational safety is while working in this field is must